Psychological Stress Delays Periodontitis Healing in Rats: The Involvement of Basic Fibroblast Growth Factor - Ya-Juan Zhao; Qiang Li; Bai-Xiang Cheng; Min Zhang; Yong-Jin Chen (Mediators of Inflammation)
Objective. To evaluate the effects of psychological stress on periodontitis healing in rats and the contribution of basic fibroblast growth factor (bFGF) expression to the healing process. Methods. Ninety-six rats were randomly distributed into control group, periodontitis group, and periodontitis plus stress group. Then, the rats were sacrificed at baseline and week(s) 1, 2, and 4. The periodontitis healing condition was assessed, and the expression of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and bFGF were tested by immunohistochemistry. Results. The stressed rats showed reduced body weight gain, behavioral changes, and increased serum corticosterone and ACTH levels (). The surface of inflammatory infiltrate, alveolar bone loss, attachment loss, and expression of IL-1β and TNF-α in the stress group were higher than those in the periodontitis group at weeks 2 and 4 (). Rats with experimental periodontitis showed decreased bFGF expression (), and the recovery of bFGF expression in the stress group was slower than that in the periodontitis group (). Negative correlations between inflammatory cytokines and bFGF were detected. Conclusion. Psychological stress could delay periodontitis healing in rats, which may be partly mediated by downregulation of the expression of bFGF in the periodontal ligament.